Financial Access 2009 : Measuring Access to Financial Services around the World - Consultative Group to Assist the Poor (Consultative Group to Assist the Poor/The World Bank, Washington, DC, 2013)
Financial Access 2009 introduces the latest data from a survey of financial regulators in 139 countries. It presents indicators of access to savings, credit, and payment services in banks, and in regulated nonbank financial institutions. It is intended for a broad audience of policymakers, researchers, practitioners, multilateral and bilateral investors, in order to guide monetary policy, monitor systemic risks, and collect information on the values of deposits and credit. This report reviews three interventions: disclosure requirements, interest rate caps, and methods to address excessive lending that can result in consumer indebtedness. Improved transparency and disclosure allow borrowers to make informed choices and can facilitate competition in financial markets, eventually leading to lower prices and improved products. Policies to restrict interest rates or credit quantity, especially in consumer credit, seem to have limited effect but require further analysis.